Organ trafficking and human trafficking for the purpose of organ removal, two international legal frameworks against illicit organ removal. Issue 3 (September 2019) - Gawronska, Sylwia
Although illicit organ removal is not a new crime, globalisation and economic inequality, underpinned by shortages of organs, have amplified this problem to such an extent that governments are now urged to take comprehensive punitive measures. Some manifestations of illicit organ removal are already considered criminal offences under domestic transplant legislations and under the framework of human trafficking. At the same time, illicit organ removal has also been categorised as a form of organ trafficking by the Council of Europe Convention against Trafficking in Human Organs, which calls upon governments to establish as a criminal offence a broad range of illicit organ- and transplant-related activities. As the crime of illicit organ removal lies at the centre of both human trafficking and organ trafficking, questions arise as to the exact differences between the two frameworks, their overlaps and their legal consequences. This article aims to provide answers to those questions by conducting a comparative analysis of both legal frameworks in terms of their development, scope, criminal law provisions and implementation. This analysis is followed by an examination of their overlaps and the consequences of prosecuting under either framework. A set of recommendations is presented aimed at implementing both legal frameworks in a way that guarantees effective prosecution while maximising the protection of victims.